INFLUENCE OF EARTH COMPOSITION ON ADSORPTION CAPACITY OF METHYLENE BLUE DYE - Tereza Plaček Otcovská; Barbora Mužíková; Pavel Padevět (Acta Polytechnica CTU Proceedings)
Final properties of unfired earth are influenced by composition of earth mixtures. Methylene blue test could be useful method for analysis of earth composition. This would facilitate of designing unfired earth building structures because composition of natural earth is various. Principle of methylene blue test is measure of amount of adsorbed methylene blue dye by clay. The essential component of earth mixtures is clay because clay fulfils a function of binder. Experimental measure of adsorption capacity of individual kind of clay is described in this paper. Adsorption capacity was investigated in montmorillonite, kaolinite, illite-kaolinite and illite clays. The obtained results show that the adsorption capacity of clays is significantly different.